Preclinical pharmacological profiles of cofrogliptin, a novel and bi-weekly DPP-4 inhibitor - Gou, Xiaoli; Dou, Caixia; Tang, Pingming; Zheng, Xiaoxiao; Zhang, Chen; Wang, Jianmin; Meng, Qingyuan; Wang, Ju (Frontiers in Pharmacology, 2026)
ObjectiveDPP-4 inhibitors are now established agents for glycaemic control in diabetes. Herein, this study systematically characterized cofrogliptin and elucidated its pharmacology, pharmacokinetics, and therapeutic efficacy for type 2 diabetes.MethodsIn vitro pharmacological characterization of cofrogliptin was performed using recombinant enzyme inhibition assays, serum/plasma DPP-4 inhibitory activity profiling, and the SafetyScreen panel. In vivo DPP-4 inhibitory potency was evaluated via measurement of serum DPP-4 activity in ICR and ob/ob mice following a single oral administration of cofrogliptin. Additionally, the oral glucose tolerance test was conducted in ICR and db/db mice pre-treated with a single oral dose of cofrogliptin. For assessment of chronic therapeutic efficacy, ob/ob mice were used with intermittent dosing to simulate prolonged diabetes management. Finally, a translational pharmacokinetic-pharmacodynamic relationship was established across rats, dogs, and monkeys to elucidate the mechanistic basis of cofrogliptin’s long-acting therapeutic benefits.ResultsThe findings have revealed that cofrogliptin is a potent and selective DPP-4 inhibitor with an IC50 of 10.80 nM in the recombinant DPP-4 enzyme assay. In ob/ob mice, it exerted favorable anti-diabetic effects, superior to those of MK3102. Furthermore, cofrogliptin exhibited a robust PK-PD relationship across rats, dogs, and monkeys. Notably, following a single oral dose of 10 mg/kg cofrogliptin, monkeys exhibited sustained DPP-4 inhibition of approximately 80% through day 14. Specifically, cofrogliptin exhibited superior pharmacokinetic profiles compared to MK3102 in rodents, whereas its PK characteristics in non-rodents were comparable to those of MK3102. Based on allometric scaling analyses, cofrogliptin is predicted to display superior human pharmacokinetic properties relative to MK3102, with anticipated longer-acting features that align with its clinical dosing frequency.ConclusionConsequently, as the only approved bi-weekly DPP-4 inhibitor, cofrogliptin is well-positioned to substantially improve medication adherence among patients with type 2 diabetes, thereby improving therapeutic outcomes.